An Analysis of Kindergarten Teachers' Attitudes towards Early Childhood Sexual Education based on Azwar's Attitude Theory - Tia Salmah Paujiah; Lutfi Nur; Qonita Qonita (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Early childhood sexual education is an essential preventive effort to protect children from sexual violence and to form body awareness and a sense of security from an early age. Kindergarten (TK) teachers play a strategic role in delivering this education, but its implementation in Indonesia still faces obstacles, especially due to the ambivalent to negative attitudes of teachers. This study aims to analyze the attitudes of kindergarten teachers towards early childhood sexual education through a systematic literature study approach. A total of 15 national and international scientific articles were reviewed using a thematic approach based on Azwar's attitude theory, which includes three dimensions: cognitive, affective, and conative. The results of the study showed that in the cognitive dimension, teachers still have a wrong and limited understanding of the concept of sexual education. In the affective dimension, teachers showed feelings of discomfort, shame, and fear, which were influenced by cultural and religious values. While in the conative dimension, teachers tended to be passive and avoided sexual topics in learning. However, several interventions such as training and the use of educational media have been shown to improve teacher readiness. This study emphasizes the importance of systematic training, policy support, and contextual pedagogical approaches to strengthen teachers' attitudes towards early childhood sexual education as a whole.